Design and application of low temperature co-fired ceramic substrates for sensors in road vehicles - Horváth, Eszter; Török, Ádám; Harsányi, Gábor (Transport, 2013)
Nowadays low temperature co-fired ceramics (further on: LTCC) are used in sensor technology as sensors and actuators. Sensors and actuators are playing an important role in intelligent road vehicles. These sensors and actuators are built up by LTCC Microsystems. The processing of starch powder and polymer based on sacrificial layer for fabrication of microfluidic structures of LTCC is described in this paper. In order to determine the optimal lamination parameters the quality of the structure was examined for 30 different temperature-pressure-time adjustments. Samples were examined by scanning acoustic microscope to detect the subsurface delamination and internal inhomogenities. The acoustic microscopic image of each sample from different lamination method was evaluated by image processing algorithm in MATLAB environment.First Published Online: 03 Apr 2013